Settler colonial logics and the neoliberal regime. (2nd April 2016) - Lloyd, David; Wolfe, Patrick
Abstract : It is often assumed that while both capitalism and the modern state may originate in processes such as primitive accumulation, imperialism and colonialism, and conquest, modernization in both the political and economic spheres gradually leaves those stages behind, allowing for some form of cosmopolitan transnational globality to emerge. In particular, settler colonialism and primitive accumulation have been understood to belong to early stages of capital expansion and accordingly to be formations lodged in the past. This introduction argues that the ongoing history of settler colonialism forms a crucial terrain through which to understand military occupation and the formations and practices of the neoliberal state that has emerged to regulate and promote a new regime of accumulation. It also explores the ways in which the formations of the contemporary state, whether military, economic, political, legal or cultural, may remain grounded in apparently peripheral or outmoded modes of domination. Understanding the neoliberal regime of accumulation in terms of its continuing debt to such histories will have a crucial bearing on the organization and articulation of resistance and dissent in the present.